Pengaruh Konsentrasi Getah Pohon Kayu Jawa (Lannea Coromandelica) Terhadap Konduktivitas Membran Blend Kitosan-Polivinil Alkohol-Litium Sebagai Membran Elektrolit - Masriana, Masriana; Napitupulu, Mery; Gonggo, Siang Tandi (Jurnal Akademika Kimia, 2017)
This research aims to study the concentration effect percentage weight of kayu jawa latex on the conductivity of membranes made from chitosan-PVA-lithium. The ionic conductivity of the membrane chitosan-PVA-lithium-latex kayu jawa was measured by impedance spectroscopy. The measurement results showed that membrane with the addition of 15% latex kayu jawa provided the highest conductivity values of 10.99353 x 10-4 S/cm. Characterization of the polymer electrolyte batteries that made from chitosan-PVA-lithium with the addition of latex kayu jawa have voltage of 1.5 Volts compared to commercial batteries that have tension was 1.5 Volts. These results indicated that latex kayu can be used as a filler to increase the ionic conductivity.